x(q+r)=s

Simple and best practice solution for x(q+r)=s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(q+r)=s equation:


Simplifying
x(q + r) = s
(q * x + r * x) = s
(qx + rx) = s

Solving
qx + rx = s

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-1rx' to each side of the equation.
qx + rx + -1rx = -1rx + s

Combine like terms: rx + -1rx = 0
qx + 0 = -1rx + s
qx = -1rx + s

Divide each side by 'x'.
q = -1r + sx-1

Simplifying
q = -1r + sx-1

See similar equations:

| 6x+-9+11x=32-12*4x | | 4x+6=-7+2x+25 | | 14+3n=8n-3x+10 | | -5+7x+8=6x-4-10x | | 4x-3=6x-12 | | 16q^2-47q-3=0 | | 12(x+3)2-21(x+3)whenx=-4 | | j^2-7j=0 | | 6.3=x-4.5 | | 0=-8-23x+3x^2 | | 35x^2-71x+24= | | 3x-8x^2=0 | | 2.5-x=3 | | 21/5-X=3 | | t^2-24t=0 | | 3x^2-23-8=0 | | 8(w+8)-(-7w-9)=14w | | -7c+5c= | | y^2-18y+17=0 | | 2xsquared=18 | | 4(y-7)=2y-83 | | 26=X/6+5 | | t^2-22t=0 | | 6x-15x+21x= | | 2x-5+1/3-x-5=61 | | 3x-5x+2=8-15+7x | | 80x=60*7.5 | | 7x+5(-3x-4)=-21-7x | | 6g-3-4-6g= | | 6/5+4/10=32/10 | | h=2+20t-5t^2 | | 5x-8+9x=6-4x-6 |

Equations solver categories